Satisfaction of Cooperative Services in The Digital Era - Gairah Sinulingga; Joko Sutisno; Adi Suryo Hutomo; Agung Sutoto (Journal of Industrial Engineering and Management, 2023)
The Digital Era is when all activities become efficient and effective by utilizing the results of technological developments in the economy. Cooperatives as an economic-institutions can also take advantage of business applications to improve service quality, which impacts in-creasing member satisfaction. This study aims to produce information in the form of a more in-depth explanation of the effect of service quality on the satisfaction level of Cooperative Members. And obtain the results of processed data about how much influence service quality has on the level of satisfaction of Cooperative Members in Depok Municipality. The research method used in this study, the data obtained, both quantitative and qualitative in nature, were examined using a descriptive verification method, namely by interviewing and giving questionnaires to 87 respondents, members using the probability sampling method, as a means to obtain accurate data. Data is processed using the SPSS 22.00 series application. The study results the show that service quality influences the level of satisfaction with a complete presentation of 22.1%, and other factors influence the rest at 77.9%. Correlation analysis obtained an R-value of 0.470. It can be concluded that there is a relationship between Service Quality and Member Satisfaction Level. The regression equation yields Y = 2.206 + 0.453X; it is supposed that if there is no Service Quality, then the Member Satisfaction Level remains at 2.206. The hypothesis is proven by the regression coefficient of the independent variable with the t-test; the result is that the coefficient of variable X on transac-tion satisfaction is significant. It can be seen that the value of the count of 4,905 ttable1,988, eye H0 rejected and H1 accepted.